Ineffective Agricultural Advisors (AAs) Support on Climate Information and Adaptation Strategies Dissemination in Ugu District, KwaZulu-Natal - Ncoyini-Manciya Zoleka; Manciya Sixolise (SAGE Open)
There is growing concern that climate change will worsen poverty and food insecurity, particularly in developing countries, hindering the achievement of Sustainable Development Goals (SDG) 1 (No Poverty) and 2 (Zero Hunger). Rural populations are expected to be severely impacted, as 75% of the poorest people in these areas, especially in Africa, depend primarily on agriculture. Although adopting precision agriculture and smart farming has been recommended to counter the adverse effects of climate change on food production, farmers continue to face increasing challenges from climate change despite support from Agricultural Advisors (AAs). The study intended to assess the support provided by AAs in the study areas, focusing mainly on the dissemination of climate information to farmers. This study employed a qualitative research design, collecting data from six focus group discussions in Ezinqoleni and uMzumbe local municipalities in the Ugu district of KwaZulu-Natal. The data were analyzed using reflexive thematic analysis with NVivo14 software. Results indicate that while smallholder farmers in the study area are aware of climate change, they lack access to relevant information to help them cope and adapt. The study also reveals that AAs in these areas are not providing useful information or advice to assist farmers in adapting to climate change, leaving them vulnerable to its adverse effects. The study strongly recommends that as South Africa is currently developing climate change policy the capacity building of AAs should be the priority. By providing high-quality climate information inclusive of sustainable adaptation strategies, farmers will better understand the importance of prioritizing climate change adaptation.